TRENDS IN CARBON DISCLOSURE RESEARCH: A BIBLIOMETRIC ANALYSIS - Kemala Octisari, Sully; Bambang Agus Pramuka; Puji Lestari (Universitas Tidar, 2023)
Carbon disclosure is a company's voluntary disclosure related to the environment and greenhouse gas emissions. With increasing global warming and global public concern about the low-carbon economy, disclosing company information related to carbon emissions is one of the main focuses for investors. This article aims to look at research development trends in the field of carbon disclosure over the last 10 years using bibliometric analysis. The data in this study were sourced from the Scopus database and analyzed with the help of the Bibliomagika 1.8 application and the Biblioshiny of Bibliometrix R-package. A search in the Scopus database was carried out with the keyword